2014
DOI: 10.1292/jvms.14-0140
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Loop-Mediated Isothermal Amplification Method for Detecting <i>Streptococcus equi</i> subsp. <i>zooepidemicus</i> and Analysis of Its Use with Three Simple Methods of Extracting DNA from Equine Respiratory Tract Specimens

Abstract: Streptococcus equi subsp. zooepidemicus (S. zooepidemicus) is a dominant pathogenic bacterium in equine pneumonia. We developed a specific loop-mediated isothermal amplification (LAMP) method, which targets the gene encoding sorbitol-6-phosphate 2-dehydrogenase (sorD), for detecting S. zooepidemicus and examined the clinical efficacies of its use in combination with each of 3 DNA extraction methods easily used by veterinary practitioners, namely the Loopamp PURE DNA Extraction Kit, InstaGene Matrix and a conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Certain LAMP primers with Csa DNA polymerase will amplify non-specific DNA even from distilled water, whereas non-specific amplification is not observed in with Bst DNA polymerase under the same conditions (data not shown). Moreover, it has been reported that in cases with low pathogen quantity, the sensitivity of LAMP using DNA extracted by the PURE Kit is less than that with DNA extracted by other kits for laboratory use [15, 19]. These findings together with our current results suggest that repeat testing is necessary to assess the optimal combination of extraction method, DNA polymerase, LAMP primers, reaction solution and colorimetric indicator.…”
Section: Discussionsupporting
confidence: 58%
“…Certain LAMP primers with Csa DNA polymerase will amplify non-specific DNA even from distilled water, whereas non-specific amplification is not observed in with Bst DNA polymerase under the same conditions (data not shown). Moreover, it has been reported that in cases with low pathogen quantity, the sensitivity of LAMP using DNA extracted by the PURE Kit is less than that with DNA extracted by other kits for laboratory use [15, 19]. These findings together with our current results suggest that repeat testing is necessary to assess the optimal combination of extraction method, DNA polymerase, LAMP primers, reaction solution and colorimetric indicator.…”
Section: Discussionsupporting
confidence: 58%
“…In recent years, LAMP has been applied clinically as a method for rapid detection of various equine pathogens. 11,12,17 Herein we report on the development of a LAMP method specific to R. equi that targets vapA to diagnose R. equi pneumonia more easily and quickly than can PCR methods.…”
mentioning
confidence: 99%
“…Although the boiling method proved useful for the LAMP assay in the current study, other commercially available DNA extraction methods f,h have decreased the false-negative results more than the boiling method in a prior study of a LAMP assay for Streptococcus equi . 11 Therefore, the other commercially available methods might be more efficient depending on certain sample types (e.g., fecal samples and abscess material).…”
mentioning
confidence: 99%
“…We therefore considered a concentration of greater than 1 × 10 4 CFU/mL in clinical samples from equine respiratory tracts to be of clinical importance. We extracted bacterial DNA from clinical samples by using a Loopamp PURE DNA Extraction Kit (Eiken Chemical), which is suitable for equine respiratory specimens . We then used the extracted DNA in each LAMP assay.…”
Section: Primer Sets Used In This Studymentioning
confidence: 99%
“…The six LAMP assays can be performed at the same temperature (65°C). In addition, because a reaction temperature of 65°C is also used in the LAMP assay for S. zooepidemicus , which is the dominant primary pathogen in bacterial pneumonia of the adult horse, the six LAMPs described here can be run simultaneously with the LAMP for S. zooepidemicus . In this way, it is possible to concurrently perform LAMP assays to detect both the primary and secondary causative pathogens of lower respiratory bacterial infections in horses in only 60 min with the naked eye; this will make it possible to institute appropriate antimicrobial therapies more quickly in horses with secondary bacterial pneumonia.…”
Section: Primer Sets Used In This Studymentioning
confidence: 99%